The abundance of zooxanthellae on massive and branching coral reefs at Bama Beach, Baluran National Park, Situbondo, East Java - Widhi, Raut Nugrahening; Paluphi, Raut Wahyuning; Azis, Muh. Aksa; Abubakar, Salim; Sunarti, Sunarti (Depik, 2025)
Zooxanthellae are single-celled microalgae that live symbiotically in coral tissue. The porpose of this study was to determine the abundance of zooxanthellae in massive and branching corals. The research method used was descriptive analysis. The sampling technique used direct field sampling by chisels, both on massive coral reefs or branching coral reefs. Observation of zooxanthellae was conducted in the laboratory using a microscope. The results obtained from the research indicate that massive corals have a relatively higher abundance of zooxanthellae with values of 109 x 105 cells/cm than branching corals with values of 73 x 105 cells/cm. In addition, massive corals are more resistant to bleaching than branching corals due to their large reserves of zooxanthellae and their ability to adapt to environmental stress.Keywords:AbundanceZooxanthellaeMassiveBranching